The relationship between acceptance of mobile technology and perceived work performance improvement among employees at AIMS-Global Holding Sdn. Bhd / Nurul Atiqah Mohd Basar - Mohd Basar, Nurul Atiqah (2019)
This research investigated the relationship between acceptance of mobile technologies and perceived work performance improvement at Aims-Global Sdn. Bhd. in Terengganu. The research was applied UTAUT model that consists of four independent variables namely performance expectancy, effort expectancy, facilitating conditions, and social influence and one dependent variable which is perceived work performance improvement. The sampling technique that was used is a stratified random sampling. The researcher used questionnaires as the instrument for primary data collection. The objective of this research is to study the relationship between acceptance of mobile technology and perceived work performance improvement among employees at Aims-Global, Terengganu. The second objective is to identify the most important variable of mobile technology acceptance toward perceived work performance improvement. The methodology used in this study discussed and explain through research design, sampling frame, population, sample technique, sample size, unit of analysis, instrument, data collection procedures, and data analysis. A total respondent in Aims-Global, Terengganu is 108 respondents. The statistic of data analysis is using a Pearson Coefficient Correlation to identify the relationship between acceptance of mobile technology and perceived work performance improvement and the descriptive analysis was used to measure the mean values. Finding on the study, the respondents agree that there are significant relationships between Performance Expectancy, Effort Expectancy, Facilitating Conditions, Social Influences and Perceived Work Performance Improvement